Research on the Transformer Intelligent Operation and Maintenance System Based on the Graph Neural Network - Chen, WenGang; Luo, DianSheng; Fu, FangYu; He, HongYing; Zhang, Ke (Frontiers in Energy Research, 2022)
With the development of smart grid and energy Internet, the power industry generates huge, multi-source, heterogeneous and highly coupled data, which is difficult to utilize. The intelligent operation and maintenance system of power transformer based on knowledge graph and graph neural network is developed in this paper. The multi-source heterogeneous data is structured and modeled by the constructed knowledge graph and it presents the correlation between data more intuitively. On this basis, the graph neural network is designed to achieve the predict and excavate the deep information hidden in the data. The testing results show that the system has fully used the multi-dimensional and interrelated heterogeneous data, achieves deeply information mine. It benefits the management and strategy implementation for the system scientifically, guide the operation and maintenance of the transformer. The system is of great significance on improving the efficiency of the transformer maintenance and safe operation.